2014
DOI: 10.3844/ajabssp.2014.503.509
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATING THE SENSITIVITY OF <i>PSEUDOMONAS AERUGINOSA</i>, <i>ESCHERICHIA COLI</i> AND <i>SALMONELLA TYPHI</i> TO VARIOUS BRANDS OF AMPICILLIN AND AMOXICILLIN AVAILABLE IN NIGERIA

Abstract: The failure of antimicrobial agents in the treatment of some ailments has become a great concern to health care practitioners. This could be as a result of low quality drugs, sneaked into the market by those who fake them, thus, this study was carried out to evaluate the sensitivity of various brands of Amoxicillin and Ampicillin on clinical isolates of Escherichia coli, Pseudomonas aeruginosa and Salmonella typhi. The test organisms were clinical bacterial isolates obtained from clinical samples from four hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Our media pH was 7.4 and the MIC value of 1.56 µg/mL was close to their results. Anomohanran et al [ 37 ] have evaluated the sensitivity of E . coli , P .…”
Section: Resultsmentioning
confidence: 99%
“…Our media pH was 7.4 and the MIC value of 1.56 µg/mL was close to their results. Anomohanran et al [ 37 ] have evaluated the sensitivity of E . coli , P .…”
Section: Resultsmentioning
confidence: 99%
“…The percentage values of the antimicrobial susceptibility obtained in this study have shown clearly that patients and health care providers can as a matter of facts rely or depend on this antimicrobial agent in the treatment of ailments associated with Streptococcus pneumoniae and Staphylococcus aureus provided it is of good quality. The reason which could be adduced for the high efficacy of Ofloxacin unlike other antibiotics which shows lower efficacy according to the findings of Anomohanran et al (2014) is that Ofloxacin is less frequently used when compared to most antibiotics available in pharmaceutical shops.…”
Section: Resultsmentioning
confidence: 99%